INTERPRETING SKILLS FOR TRANSLATORS - Abduraxmonov Toʻraxon,; Shuxratova Muattaroy Muxammad qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article discusses the interpreting skills necessary for translators, arguing  that  incorporating  interpreting  competencies  can  significantly  improve translators'  responsiveness,  cognitive  flexibility,  and  cultural  adaptability.  Key interpreting skills such as active listening, memory retention, real-time reformulation, and  intercultural  awareness  are  analyzed  in  the  context  of  how  they  support  the translator’s role in both written and spoken communication. The study concludes with recommendations for translator training programs to integrate interpreting practice to prepare linguists for more dynamic professional settings.